إجراءات رقابة التطبيق في ظل استخدام الحاسوب : حالة دراسية في كلية الإدارة و الاقتصاد بجامعة الموصل - انصاف محمود رشيد (PROSPECTIVE RESEARCHES, 2023)
Big and small units use information technology in operation and processing deter, because the accounting and controlling require high speed in doing financial operations, the need for computer gets bigger in order to reduce the time and effort spent by the account and the person who checks in doing their works. As for as inside control is concerned the use of computers has participated in achieving the goal of control systems in an effective way, especially with those of the direct controlling on the accounting applications which is related to the activity of unites which contains controlling on input, output and operating. This is what the research deals with through introducing the concept of application controlling and its procedures and evaluating its procedures and study at the college of economy and administration university of Mosul.